PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PKn DENGAN PENDEKATAN COOPERATIVE TIPE STAD DI KELAS IV SD - Julaili, Julaili (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The problems which consist of in study of Pendidikan Kewarganegaraan in  elementary school especially class of IV often in causing by dominant teacher use method deliver a lecture dalan process study. Though if when in ;ihat of facet of maeri the study can in teaching with method outside discourse, as a result given by study is teacher lose looks enthusiasm learn student. For overcome the problem, teacher shall earn to create atmosphere draw attention and student to tickle to involve active in activity of study. Approach of Cooperative learning represent one of the approach of study of which can train student to learn self-supportingly in group, because in this approach of student will learn in its group with is assisting each other one another.   Kata kunci : pembelajaran, pendekatan, STAD, hasil belajar